"Anything that Benefits the Workers Should Benefit the Client": Opportunities and Constraints in Self-Directed Care During the COVID-19 Pandemic. (April 2023) - Wendel, Carrie L.; LaPierre, Tracey A.; Sullivan, Darcy L.; Babitzke, Jennifer; Swartzendruber, Lora; Barta, Tobi; Olds, Danielle M.
Self-directed care (SDC) models allow Home and Community Based Services (HCBS) consumers to direct their own care, thus supporting flexible, person-centered care. There are many benefits to the SDC model but access to resources is essential to successful outcomes. Considering the autonomy and flexibility associated with SDC, it is important to understand how SDC responded to the COVID-19 pandemic and the resources available to help manage this situation. We conducted 54 in-depth interviews with HCBS consumers, direct support workers, family caregivers, and providers to examine the impact of COVID-19 on HCBS services in Kansas. Findings illuminate how self-directed consumers carried a lot of employer responsibility, with limited resources and systemic barriers constraining self-determination and contributing to unmet care needs, stress, and burden. Policy flexibilities expanding the hiring of family members were beneficial but insufficient to address under-resourced working conditions and labor shortages that were exacerbated by the pandemic.